An overview of methods used for the detection of aquatic resource consumption by humans: Compound-specific delta N-15 analysis of amino acids in archaeological materials. (April 2016) - Naito, Yuichi I.; Bocherens, Hervé; Chikaraishi, Yoshito; Drucker, Dorothée G.; Wißing, Christoph; Yoneda, Minoru; Ohkouchi, Naohiko
Abstract: The detection of aquatic resource consumption is important in paleodietary studies as it provides insights into the adaptive strategies of modern humans. Debate as to whether or not it is a recent innovation in hominid evolution also emphasizes its importance to the field. Stable carbon and nitrogen isotope analysis of bulk collagen has been powerful tool for the investigation of ancient human diet, especially for the detection of marine food consumption. However, the nitrogen isotopic composition could significantly vary even within the same animal species depending on environmental conditions, making a dietary reconstruction based on human remains difficult without enough specimens of referential animal prey. Nitrogen isotope analysis of individual amino acids in bone collagen has recently been proposed as a potentially useful technique for the detection of not only marine resources in diets but also freshwater ones. In this paper, we further test its applicability to human populations in a variety of regions and chronological time periods in the world. We found that: (i) irrespective of climatic conditions, nitrogen isotopic compositions of glutamic acid and phenylalanine of terrestrial animals group similarly; (ii) these two amino acids are particularly useful to detect marine or freshwater resource consumption; (iii) a multinomial logistic regression based on some combinations of isotope indicators successfully distinguishes aquatic and terrestrial animals; (iv) detection of aquatic resource consumption by prehistoric humans could be possible based solely on the isotopic compositions of human remains, even in the absence of coeval potential prey. This approach is therefore promising for the paleodietary reconstruction of isolated human remains with few associated faunal remains from archaeological sites. Highlights: Amino acid δ 15 N values for archaeological materials are reviewed. Aquatic fauna are generally distinguishable from terrestrial fauna. Aquatic food consumption can be detected if several isotopic tracers are used.